ARTIFICIAL INTELLIGENCE BASED SMART WALKING STICK - P.Vamsi Krishna (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper shows the Smart Walking Stick based on Ultrasonic sensors and Arduino for Visually Impaired.There are roughly 37 million individuals over the globe who are visually impaired as indicated by the World Health Organization. Individuals with visual inabilities are regularly subjected to outer help which can be given by people, trained dogs or electronic gadgets for basic assistance. We proposed least effort and light weight structured with microcontroller that processes signal and alerts the visually impaired person over any obstacle, water through beeping sounds or vibrations. The system comprises of ultrasonic and infrared sensors for process of receiving, processing and sending signals to the alarm system which finally alerts the user for action. The system will revolutionize the lives of the blind people. The main objective is to provide more mobility and independency to blind people.